The impact of elements and advertising broadcasting intensity exposure in terrestrial radio - Harliantara, Harliantara; Maella, Nurannafi Farni Syam; Junaedi, Ari; Abror, Dhimam; Chen, Lu Hui (Jurnal Studi Komunikasi, 2023)
Advertising is appealing to most organisations since it provides information, entertains, and communicates, especially on the radio. Advertising can boost sales, but it must be carefully structured to be effective. Radio advertisers must create engaging messaging to be effective. Selective attention, Selective perception, and Selective retention are the three ways people pick mass media content. Selective attention occurs when people focus on interesting messages. Selective perception means people interpret messages according to their ability. Selective retention is when a person only remembers the message they want. Radio advertising has several qualities and tools, which can be divided into Message Style, Message Structure, and Presenter. Radio advertising messages are readily forgotten since they function on the right side of the brain and excite more impulse nets, so they must be repeated. According to current studies, improving the Radio Advertising Components (Message delivery style, Message Structure, and Message Conveyor) by 0.125 times will enhance audience attention. Under the same conditions, increasing radio ad frequency and duration by 0.0512 times decreases audience interest. Increased radio advertising intensity decreases audience interest. Nonetheless, this may happen because field surveys suggest audiences are happier or more interested in listening to high-quality radio ads by paying special attention to radio ad aspects. Radio advertisement broadcasting is intense and plays low-quality ads, which displeases audiences.